EFFECT OF SEED PRE-SOWING TREATMENTS ON THE GERMINATION AND EARLY GROWTH OF ALBIZIA LEBBECK SEEDS - Joyce KWAKYE; Sydney Stanley BLANKSON (Journal of Applied Life Sciences and Environment)
Albizia lebbeck is a multipurpose tree that has many benefits for the environment and the end user. The extent to which this tree species is cultivated is very low due to seed coat dormancy, which causes a longer germination period and late seedling growth. This research was done at Kwame Nkrumah University of Science and Technology, located in Kumasi, Ghana, at the Department of Horticulture, to ascertain the effect of seed pretreatment on germination and early seedling growth. Germination was observed in seeds pretreated with hot water (100º) for 1 minute (T1), dry heat (90º) for 2 minutes (T2), in 6% hydrogen peroxide solution for 30 minutes (T3), cold water at room temperature for 24 hours (T4) and untreated seed (T5) as the control. The experiment was conducted using a randomised complete block design (RCBD) with three replications. The data obtained for seed germination percentage were statistically analysed using one-way analysis of variance in Statistix 7.0 software, and the least significant difference at 5% probability level was used to separate the means of height, collar diameter and number of leaves. A comparison between the pretreated and control seeds showed no significant difference (P > 0.05) on germination percentage, germination rate, and root and shoot dry weights of Albizia lebbeck. However, it had a positive influence (P < 0.05) on early growth characteristics. Seeds soaked in cold water (T4) had maximum early seedling growth. Hydrogen peroxide treatment (T3) yielded the highest collar diameter growth. Hot water treatment (T1) had the lowest height, collar diameter and number of leaves. Cold water at room temperature should be encouraged as a pretreatment method for the early growth of Albizia lebbeck seedlings.